1978
DOI: 10.1111/j.1745-4603.1978.tb01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical Aspects of Soy Proteins Structure Formation

Abstract: Mechanisms involved in the formation of three‐dimensional networks of globular proteins are discussed in general terms. Denaturation and aggregation of soy proteins under various conditions were studied. Differential scanning calorimetry was used in the denaturation, and turbidity measurements in the aggregation studies. Conditions favoring denaturation, such as high and low pH, had the opposite effect on aggregation. Salt was found to have a special effect on the behavior of soy proteins, suppressing aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
173
0
5

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(210 citation statements)
references
References 40 publications
32
173
0
5
Order By: Relevance
“…Between 70 and 80ºC, soybean β-conglycinin was thermally denatured, but glycinin was not, according to the result of DSC (Hermansson, 1978;Zhang et al, 2004). For one-step heating, these data lead to the hypothesis that the combination of denatured β-conglycinin and native glycinin lower the dispersion stability of soymilk, whereas the combination of denatured β-conglycinin and denatured glycinin increase dispersion stability.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Between 70 and 80ºC, soybean β-conglycinin was thermally denatured, but glycinin was not, according to the result of DSC (Hermansson, 1978;Zhang et al, 2004). For one-step heating, these data lead to the hypothesis that the combination of denatured β-conglycinin and native glycinin lower the dispersion stability of soymilk, whereas the combination of denatured β-conglycinin and denatured glycinin increase dispersion stability.…”
Section: Resultsmentioning
confidence: 95%
“…These data clearly showed that heat treatment of soymilk at temperatures higher than 90ºC increased the dispersion stability of soymilk protein or soymilk emulsion consisting of proteins and lipids. For soybean protein dispersion (Hermansson, 1978) and soymilk (Zhang et al, 2004), β-conglycinin and glycinin were reported to be thermally denatured at approximately 70 and 90ºC, respectively, by differential scanning calorimetry (DSC). From these reports, heat treatment of soymilk at 70 or 80ºC was thought to denature only β-conglycinin, but not glycinin.…”
Section: Resultsmentioning
confidence: 99%
“…2) showed two endothermic peaks: one with a lower Td n value, corresponding to the 7S globulin; and another peak corresponding to the 11S globulin, which had already been shown to be a contaminant in the SDS-PAGE analysis [21][22][23][24]. In the thermogram of the 7St sample, the endothermic peak that was attributed to the 11S globulin disappeared, whereas the other endotherm showed lower Td t and ΔHd t values than its native counterpart (the 7Sn sample).…”
Section: Effect Of Acid Treatment On Interfacial and Foam Properties mentioning
confidence: 99%
“…The SPIn thermogram showed two endothermic peaks characteristic of the thermal denaturation of soybean 7S and 11S globulins [21][22][23][24]. Table 1.…”
Section: Effect Of Acid Treatment On Interfacial and Foam Properties mentioning
confidence: 99%
“…The United States Food and Drug Administration authorized the Soy Protein Health Claim on 26 October 1999 stating that 25 g of soy protein a day may reduce the risk of heart disease. Soybean foods continue to penetrate rapidly into cultures and diets since the market is very responsive to this health claim (Fukushima, 2001;Hermansson, 1978). Tofu is one of the most important traditional soy foods in the eastern world.…”
Section: Introductionmentioning
confidence: 99%